Therapy system for Cerebral Palsy patient - Tan, Qiao Juan (2016)
Cerebral Palsy is an illness which is well known by people. It has been affecting many infants. These infants diagnosed with Cerebral Palsy have to undergo treatment at the early stage in order to help them in mobility. Healthcare has been introducing many treatments to help the patient with mobility which can train them to be independent. As such there is a need to develop new equipping therapy system to meet the needs of the patient. In this project, we would be developing a mock-up massage therapy system so to help in releasing muscles stiffness and ease the pain of the patient. The therapy system would be created using servo motors and brainwave reading headset interfacing with Windows and Raspberry Pi. It would serve as a wireless therapy system for the patient. Patient could have the therapy at any time. Lastly, this would help to ease the problem in shortage of therapists.